Effect of elements on linear elastic stress analysis: A finite element approach - Wai, Chee Mun; Rivai, Ahmad; Bapokutty, Omar (Sun Publications, 2013)
The question of “what type of elements should be used?” never fails to pop up in the minds of analysts when carrying out finite element analysis (FEA). Indeed, the selection of elements from a variety of different types of elements is part and partial of FEA. Initially, only one-dimensional (1D) elements were developed. The introduction of two-dimensional (2D) and three dimensional (3D) elements, which came later, greatly increase the capability of finite element (FE) programs to model and solve complex engineering problems. Not only do these elements provide improvement in accuracy of the results but also brought about new challenges which include evaluation of numerical errors, validity of results, setup and execution time as well as large computer memory capacity. The outcome of the analysis is very much dependent of the type of element chosen. The aim of this paper is to investigate the factors influencing the selection of elements in FEA by considering the effects of different types of elements on the results of FEA. A simple case study of an I-beam subjected to an asymmetric load is carried out by FEA. Three different models of the I-beam were prepared and analyzed separately using 1D elements, 2D elements, and 3D elements. The results of these models were compared with the mathematical model of the I-beam. The FEA results of these models showed good agreement with the theoretical calculation despite the small and negligible errors in the analysis. Since the aim of FEA is an effective and efficient solution to engineering problems, it becomes a necessity to consider factors such as structural shape, desired analysis results, and computer capability while choosing the right element for the analysis.